Gestão em áreas de risco de enchentes: estudo de caso para União da Vitória - Paraná - Rocha, Paulo Sergio Meira (2012)
All around the planet, the occupation of floodplains aggravates social, economical, and environmental problems, due to the floods which frequently occur in these areas. Most Brazilian cities do not impose restrictions on the occupation of areas at risk of flooding, especially in what concerns the division of land into parcels or lots, which in turn becomes the most evident cause of inappropriate occupation of urban and riparian land. This work, regarding the management of flood risk areas, was developed at União da Vitória, State of Paraná. Located in the south of the State, União da Vitória has developed at the banks of the Iguaçu River, on the transition from the second to the third plateau in the State, and the main course of the river is enlarged whenever the magnitude of discharge is amplified by extreme rainfall events. The region suffered significant impact from the 1983 and 1992 floods, which caused great social, environmental and economical damage. Federal, State and Municipal governments were strongly impressed, and initiated a series of studies in search of prevention alternatives to minimize the floods impact. Several control measures were suggested in studies, aiming to minimize the impact of the Iguaçu River floods in União da Vitória. The work intends to study which flood control measures from studies have been implemented in União da Vitória after 1983, which were more efficient, and how they contribute to the planning and management of flood risk areas. By means of this research it was possible to gather and organize historical and corroborating information about the floods in União da Vitória, as well as to measure the recurrence time of floods before and after 1983. It was also possible to study and present, in one volume, twenty-eight proposals developed and presented by studies which looked for solutions for the floods, and to identify how many and which implemented measures have been more important. As a contribution, the present study proposes a set of measures for the management of floods in União da Vitória.